2014
DOI: 10.7567/jjap.53.05fl02
|View full text |Cite
|
Sign up to set email alerts
|

Growth of thick InGaN layers by tri-halide vapor phase epitaxy

Abstract: This is the first study to report InGaN growth by tri-halide vapor phase epitaxy (THVPE) using InCl3 and GaCl3 generated by the reactions between metal sources (i.e., metallic indium and gallium) and gaseous chlorine. The influence of the surface orientation of the initial substrate on InGaN-THVPE growth was investigated using freestanding (0001) and GaN substrates. Only a N-polar InGaN epitaxial layer was obtained by THVPE because of the instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
1
23
1
Order By: Relevance
“…GaN could be grown on true(10true1¯0true) − 5° off, true(10true1¯true1¯true), and (0001¯) but not on true(0001true), true(10true1¯1true), which was in agreement with the facets that appeared for the SAG by THVPE, as shown in Fig. c and d. Furthermore, our previous study revealed that GaN could not be grown on true(20true2¯1true) and (303¯1) as well as true(10true1¯1true) by THVPE . Thus, true{h0trueh¯1true} planes were not stable for THVPE condition, which caused an irregular true{h0trueh¯1true}–like shape to appear for the SAG.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…GaN could be grown on true(10true1¯0true) − 5° off, true(10true1¯true1¯true), and (0001¯) but not on true(0001true), true(10true1¯1true), which was in agreement with the facets that appeared for the SAG by THVPE, as shown in Fig. c and d. Furthermore, our previous study revealed that GaN could not be grown on true(20true2¯1true) and (303¯1) as well as true(10true1¯1true) by THVPE . Thus, true{h0trueh¯1true} planes were not stable for THVPE condition, which caused an irregular true{h0trueh¯1true}–like shape to appear for the SAG.…”
Section: Resultssupporting
confidence: 81%
“…ð and 30 31Þ ð as well as 10 11Þ ð by THVPE [17]. Thus, h0 h1 È É planes were not stable for THVPE condition, which caused an irregular h0 h1 È É -like shape to appear for the SAG.…”
Section: þ ðmentioning
confidence: 99%
“…During the bulk growth of GaN, as the crystal growth direction of conventional HVPE is along <0001> gallium polar face, the crystal diameter is reduced by inclination of the sidewall facet (10–11) or (11–22) toward the center of the substrate as growth proceeds. Herein, we propose a novel trihalide vapor‐phase epitaxy (THVPE) growth method using GaCl 3 as the Ga precursor . This method results in an enlarged crystal diameter because the GaN growth by THVPE is conducted along <000‐1>, which is the direction opposite to that in conventional HVPE, and the sidewall facet inclination occurs toward the periphery of the substrate as growth proceeds.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Therefore, the outer rim of the crystal must be ground off, that results in a reduced crystal diameter. During the bulk growth of GaN, as the crystal growth direction of conventional HVPE is along <0001> gallium polar face, the crystal diameter is reduced by inclination of the sidewall facet (10)(11) or (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) toward the center of the substrate as growth proceeds. Herein, we propose a novel trihalide vapor-phase epitaxy (THVPE) growth method using GaCl 3 as the Ga precursor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation